Association of maternal diabetes with autism spectrum disorders in offspring: A systemic review and meta-analysis. Issue 2 (January 2018) - Wan, Hongquan; Zhang, Chunguo; Li, He; Luan, Shuxin; Liu, Chang
Abstract : Abstract: Studies on the association of maternal diabetes with autism spectrum disorders (ASDs) in offspring provide inconsistent findings; therefore an updated and comprehensive literature review and meta-analysis is necessary to perform in order to evaluate the available evidences. After searching databases systematically, we established the inclusion criteria and selected the eligible studies. In both overall and stratified analyses, the estimated effects were synthesized dependent on the presence or absence of heterogeneity. Twelve articles involving 16 studies were included and synthesized, demonstrating a significant association of maternal diabetes with ASDs among children (relative risk [RR] = 1.48). However, high heterogeneity was observed ( I 2 = 56.3%) and publication bias was identified. In terms of the analyses on reliable evidences from case-control studies, heterogeneity and publication bias disappeared, and the risk of ASDs was increased by 62% among diabetic mothers compared with non-diabetic mothers. Maternal diabetes, especially gestational diabetes mellitus, is associated with ASDs in offspring based on a limited number of convincing case-control studies. More large-scale population-based prospective studies are still needed to draw firm conclusions.